2000
DOI: 10.1046/j.1523-1747.2000.00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Nonallelic Heterogeneity of Epidermodysplasia Verruciformis with Two Susceptibility Loci Mapped to Chromosome Regions 2p21–p24 and 17q25

Abstract: Epidermodysplasia verruciformis is a rare genodermatosis associated with a high risk of skin cancer. This condition is characterized by an abnormal susceptibility to specific related human papillomavirus genotypes, including the oncogenic HPV5. Epidermodysplasia verruciformis is usually considered as an autosomal recessive disease. We recently mapped a susceptibility locus for epidermodysplasia verruciformis (EV1) to chromosome 17qter within the 1 cM interval between markers D17S939 and D17S802. We report here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 29 publications
1
91
0
5
Order By: Relevance
“…This polymorphism is thought to be located in a putative transmembrane domain. 4 We have found that the presence of a polymorphism in the EVER2 gene is not only associated with the presence of HPV antibodies in control subjects but also an increased risk of squamous cell carcinoma of the skin. It is possible that EVER genes are involved in controlling the HPV pathogenesis in epidermal keratinocytes or that they directly affect the innate or adaptive immune responses which may control the clearance of EV-HPVinfected keratinocytes.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…This polymorphism is thought to be located in a putative transmembrane domain. 4 We have found that the presence of a polymorphism in the EVER2 gene is not only associated with the presence of HPV antibodies in control subjects but also an increased risk of squamous cell carcinoma of the skin. It is possible that EVER genes are involved in controlling the HPV pathogenesis in epidermal keratinocytes or that they directly affect the innate or adaptive immune responses which may control the clearance of EV-HPVinfected keratinocytes.…”
Section: Resultsmentioning
confidence: 83%
“…We have shown here that a very common single nucleotide polymorphism increases the likelihood for HPV seropositivity. Although the precise role of EVER2 is unknown, EVER2 transcript has been isolated from spleen and thymus tissue, as well as from normal skin, 4,16 supporting its hypothesized role in the immunogenic response.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In general, EV shows an autosomal recessive pattern of inheritance [7]. The EV loci were mapped to chromosome 2p21-p24 (EV2) and 17q25 (EV1) [8], respectively. In the EV1 interval, 2 adjacent related genes, EVER1 and EVER2, were identified in 2002 [9].…”
Section: Introductionmentioning
confidence: 99%